CONSTITUTIONAL CONVENTION IN PRACTICE CONSTITUTION IN INDONESIA - Suprijatna, Dadang (DERECHTSSTAAT, 2015)
ABSTRACT Conventions has the same legal force by law, because it is accepted and executed, even the convention can shift the written laws. Constitution change, one of them can be reached through the convention, because the constitution is open to be evaluated and refined over time through political mechanisms. To make changes and improvements in the constitution can be developed through amendments or changes as stipulated in Article 37 of the Constitution of 1945 can also be done through a constitutional convention. Convention by constitutional law experts recognized as one of the sources of constitutional law that can be used in the preparation of the implementation system of the Republic of Indonesia as the law states that sovereignty of the people. Almost all modern countries in the world beside it has the constitution (the written Constitution) in the practice of state administration also acknowledges the convention. There are convention in every constitutional system, especially in democracies. For Indonesia, the convention grew by or in accordance with the needs of the Indonesian state. Therefore it should be understood that the convention can not be"imported" form the constitutional system of other countries may be different principle and character with the state system of Indonesia. Parliamentary system that has been entrenched in the constitutional system in western countries, are certainly not in accordance with the constitutional system of Indonesia under the Act of 1945. Keywords: Convention, Constitutional, Indonesias ConstitutionÂ